Social Construction and the Criminalization of Identity: State-Sanctioned Oppression and an Unethical Administration. (4th July 2018) - Gaynor, Tia Sherèe
Abstract : What is considered a crime and who is considered a criminal is largely based on social constructions that have a longstanding presence in U.S. history. In the United States, the social construction of crime and criminality is disproportionately attributed to the behaviors of those with marginalized racial, sexual, and gender identities. This article explores sources and instances of systemic injustice by making explicit connections between the social construction of crime and criminality and the criminalization of identity. Negative social constructions shape the behaviors of public actors and institutions in such a way that they serve as sources and promoters of systemic and institutional injustice.